2007
DOI: 10.1016/j.optlastec.2005.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-wave diode-pumped operation of an Yb:NaLa(WO4)2 laser at room temperature

Abstract: Room-temperature continuous-wave (cw) laser operation is demonstrated with the newly developed Yb:NaLa(WO 4 ) 2 disordered crystal by end-pumping with a fiber-coupled diode laser. A maximum output power of 330 mW is obtained with an optical efficiency of 4.9% and a slope efficiency of 6.3% with respect to the incident pump power. The efficiencies in terms of the absorbed pump power are roughly three times higher. Sellmeier dispersion curves for the ordinary and extraordinary refractive indices of the NaLa(WO 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…7 and Table III. The crystal field splitting in NaGdW is similar to that found in other Yb 3+ -doped disordered DT laser hosts 7 and comparable to the splitting in the ordered monoclinic KY͑WO 4 ͒ 2 and KGd͑WO 4 ͒ 2 . 37 The crystal field calculations presented above have determined the irreducible representations of the 2 F 7/2 ͑n͒ and 2 F 5/2 ͑nЈ͒ Stark levels as specified in Fig.…”
Section: Fig 4 Polarizedsupporting
confidence: 83%
“…7 and Table III. The crystal field splitting in NaGdW is similar to that found in other Yb 3+ -doped disordered DT laser hosts 7 and comparable to the splitting in the ordered monoclinic KY͑WO 4 ͒ 2 and KGd͑WO 4 ͒ 2 . 37 The crystal field calculations presented above have determined the irreducible representations of the 2 F 7/2 ͑n͒ and 2 F 5/2 ͑nЈ͒ Stark levels as specified in Fig.…”
Section: Fig 4 Polarizedsupporting
confidence: 83%
“…The full structure of these ceramic materials is still unknown, but the XRD measurements suggest a low symmetry. The obtained phases are isostructural and crystallize in the 5 monoclinic system. SEM images showed that the grain size varied in the range from ~1 to ~7 µm [21].…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Their interesting optical properties and variety of structure types made them very attractive materials used as scintillator detectors, solid state laser-host, and phosphors. Molybdates and tungstates doped with Nd 3+ , Dy 3+ , Ho 3+ , Er 3+ ,Tm 3+ or Yb 3+ are used as ultra-fast diode pumped solid state lasers while doped with europium trivalent ions are used in light emitting diodes (LEDs) [1][2][3][4][5][6][7][8]. For many years we have conducted optical studies of new RE 3+ -doped molybdates and tungstates having two different types of structures (scheelite or wolframite-type) [9][10][11][12][13][14][15][16] [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…400 -1700 nm, to the Sellmeier refractive index (n) normal dispersion of the form [23,24] The refractive index dispersions of investigated tellurite glasses are quite similar to each other and exhibit a very high value, greater than 2.1, considerably higher than that obtained for standard optical glasses. Differences between particular glasses (< 5%) were not considered significant since ellipsometry is not a direct method to determine the refractive index.…”
Section: Resultsmentioning
confidence: 65%